Differential concentrations of NaCl and K2Cr2O7 stress conditions: biophoton characteristics and quality prediction feasibility analysis of fresh Nepeta cataria L. leaves - Wang, Ruyu; Luan, Jiahui; Wang, Zhiying; Cao, Baorui; Chen, Yiwei; Li, Xue; Deng, Tingting; Du, Jinxin; Han, Jinxiang; Yang, Meina (Frontiers in Plant Science, 2025)
IntroductionNepeta cataria L. (NcL), a perennial medicinal plant, is used to dispel wind-heat, remove blood stasis, and reduce swelling. However, soil salinization and heavy metal pollution have severely impacted its growth and quality. Current quality assessments, based solely on pulegone (PG) content in the final product, neglect cultivation process controls.MethodsWe applied biophoton detection to differentiate stress types in fresh NcL leaves and explored the correlation between biophoton emission and plant quality. Spontaneous photon emission (SPE) and delayed luminescence (DL) were measured under NaCl and K2Cr2O7 stress. Key parameters, including counts per second (CPS) and initial intensity (I0), were analyzed. PG content was determined via ultra-high performance liquid chromatography, alongside physiological and oxidative stress indexes.ResultsStress conditions significantly inhibited NcL growth and quality, leading to marked differences in biophoton emission, physiological and biochemical indicators, oxidative stress indexes and PG content between stress and control groups. For instance, in the 120 mmol/L NaCl group, the CPS decreased by 54.27%, while I0 dropped by 54.12%. PG content in high-salinity groups was 1.22 mg/g, 40.19% lower than controls (2.04 mg/g). CPS and I0 strongly correlated with PG content (r = 0.89 and r = 0.85, respectively), as well as with physiological and oxidative indicators. These relationships were clearly visualized.DiscussionsOur study demonstrates the potential of biophoton detection for quality evaluation during NcL cultivation. We identified specific biophoton parameters that reflect plant quality, offering a new approach for process-based quality control.